Oral cancer preventive behaviors in rural women: application of the theory planned behavior - Fatemeh Mohammadkhah; Amirhossein Kamyab; Ali Khani Jeihooni (Frontiers Media S.A., 2024)
BackgroundOral cancer is becoming a primary concern for non-communicable illnesses and global health care initiatives. Low-income people, people with disabilities, the elderly, residents of detached and rural regions, and people belonging to minority groups bear a greater burden of oral diseases. The purpose of this research is to identify rural women's oral cancer prevention activities using the theory of planned behavior (TPB).MethodsThe current research is a cross-sectional analysis of 700 female hookah users who were referred to rural health facilities in Fasa and Shiraz, Fars, Iran in 2019-2020. The participants were selected by random sampling method. The TPB questionnaire and a demographic information questionnaires were the data gathering instruments used in this study to assess oral cancer prevention practices among participants. Data were analyzed by SPSS 22 using frequency, mean, and standard deviation as descriptive statistics, and Pearson correlation coefficients and linear regression as inferential statistics at a significance level of P < 0.05. The Kolmogorov-Smirnov test was used to determine whether the data were normal.ResultsThe average age of the participants was 44.54 ± 8.72 years, and the average age at which they started hookah was 23.8 ± 28.68 years. The average history of hookah use was 15.8 ± 6.65 years, and the average size of the household in the test group was 4.73 ± 1.16. The average scores of the constructs of the TPB and oral cancer prevention behaviors were average or at a low level, while nicotine addiction was relatively high. The constructs of knowledge, attitude, subjective norms, and behavioral intention are significantly correlated with oral cancer prevention behaviors in hookah-user women. There was a significant inverse relationship between nicotine dependence and oral cancer prevention behaviors, and there was a strong link between perceived behavioral control and behavioral intention (P < 0.05).ConclusionBased on the results of this study, the average scores of the structures of the TPB and oral cancer prevention behaviors were average or at a low level among rural hookah-user women, which indicates the necessity of an educational program based on this theory for rural women to adopt and maintain oral cancer prevention behaviors.